Biocontrol potential of endophytic bacterium Bacillus altitudinis GS-16 against tea anthracnose caused by Colletotrichum gloeosporioides - Wu,Youzhen; Tan,Yumei; Peng,Qiuju; Xiao,Yang; Xie,Jiaofu; Li,Zhu; Ding,Haixia; Pan,Hang; Wei,Longfeng (PeerJ, 2024)
Background As one of the main pathogens causing tea anthracnose disease, Colletotrichum gloeosporioides has brought immeasurable impact on the sustainable development of agriculture. Given the adverse effects of chemical pesticides to the environment and human health, biological control has been a focus of the research on this pathogen. Bacillus altitudinis GS-16, which was isolated from healthy tea leaves, had exhibited strong antagonistic activity against tea anthracnose disease. Methods The antifungal mechanism of the endophytic bacterium GS-16 against C. gloeosporioides 1-F was determined by dual-culture assays, pot experiments, cell membrane permeability, cellular contents, cell metabolism, and the activities of the key defense enzymes. Results We investigated the possible mechanism of strain GS-16 inhibiting 1-F. In vitro, the dual-culture assays revealed that strain GS-16 had significant antagonistic activity (92.03%) against 1-F and broad-spectrum antifungal activity in all tested plant pathogens. In pot experiments, the disease index decreased to 6.12 after treatment with GS-16, indicating that strain GS-16 had a good biocontrol effect against tea anthracnose disease (89.06%). When the PE extract of GS-16 treated mycelial of 1-F, the mycelial appeared deformities, distortions, and swelling by SEM observations. Besides that, compared with the negative control, the contents of nucleic acids, protein, and total soluble sugar of GS-16 group were increased significantly, indicating that the PE extract of GS-16 could cause damage to integrity of 1-F. We also found that GS-16 obviously destroyed cellular metabolism and the normal synthesis of cellular contents. Additionally, treatment with GS-16 induced plant resistance by increasing the activities of the key defense enzymes PPO, SOD, CAT, PAL, and POD. Conclusions We concluded that GS-16 could damage cell permeability and integrity, destroy the normal synthesis of cellular contents, and induce plant resistance, which contributed to its antagonistic activity. These findings indicated that strain GS-16 could be used as an efficient microorganism for tea anthracnose disease caused by C. gloeosporioides.
Keywords: Endophytic bacterium; Camellia sinensis; Colletotrichum gloeosporioides; Bacillus altitudinis; Biocontrol efficacy